Self-Reported Age of Onset and Telescoping for Cigarettes, Alcohol, and Marijuana Across Eight Years of the National Longitudinal Survey of Youth - Shillington, Audrey M. (2012)
Smoking, drinking, and illicit drug use are leading causes of morbidity and mortality, both during adolescence as well as later in life. Although for some adolescents, substance use may last for only a brief period of experimentation, use of these substances in adolescence may have negative consequences. The determination of how well national and local policy and intervention efforts address teen substance use depends largely on the collection of valid and accurate data. Assessments of substance use rely heavily on retrospective self-report measures. The reliability and validity of self-reported substance use measures, however, may be limited by various sources of measurement error. This study utilizes four waves of data from the National Longitudinal Survey of Youth spanning eight years. Our wave-to-wave analyses examined the accuracy of self-reported age of onset for cigarette, alcohol and marijuana users. Findings indicate that approximately one-fourth of cigarette users, one-fifth of alcohol users and one-third of marijuana users reported their age of onset exactly the same across waves. Of those who reported the age of onset inaccurately, the error tended to be in the direction of reporting their age of onset as older at a latter wave relative to what was reported previously, known as forward telescoping. Results from multiple linear regression analyses showed that the single most consistent variable associated with telescoping was the number of years since the substance was first reported. Time since first report was the single consistent and strongly associated with telescoping in each wave-to-wave comparison for all three substances under study. Implications for policy and research are discussed.